2014
DOI: 10.5430/jst.v4n1p42
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of survival in Moroccan patients with Glioblastoma

Abstract: Background: Glioblastoma is the most common and aggressive type of glioma and has the poorest survival. Some parameters have been identified as potential prognostic factors for patients with glioblastoma. The purpose of this study is to examine the influence of clinical, tumor and treatment factors on overall survival in Moroccan patients with newly diagnosed glioblastoma. Methods: In this study, we retrospectively analyzed data from 89 Moroccan patients with newly diagnosed Glioblastoma (54 males and 35 femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…The relative risk of dying was three times higher for patients with KPS score 70-80 compared to those with KPS > 80. The same outcome has also been reported in previous studies (9,11).…”
Section: Predictors Of Survivalsupporting
confidence: 90%
See 1 more Smart Citation
“…The relative risk of dying was three times higher for patients with KPS score 70-80 compared to those with KPS > 80. The same outcome has also been reported in previous studies (9,11).…”
Section: Predictors Of Survivalsupporting
confidence: 90%
“…To date, tumour grade, age, performance status and extent of resection are among the most significant predicting factors influencing survival (6,8,9). In univariate analysis, our study demonstrated that the patient factors (age, comorbidities), tumour factors (tumour grade, tumour location, lobes) and treatment factors (surgical methods, adjuvant therapy) were associated with overall survival (P < 0.05).…”
Section: Discussionmentioning
confidence: 59%